“Adaptative endovascular strategy to the CloT MRI in large intracranial vessel occlusion” (VECTOR): Study protocol of a randomized control trial - Janot, Kevin; Zhu, François; Kerleroux, Basile; Boulouis, Grégoire; Shotar, Eimad; Premat, Kevin; Eugene, François; Dargazanli, Cyril; Chalumeau, Vanessa; L’Allinec, Vincent; Benhassen, Wagih; Marnat, Gaultier; et al. (American journal of neuroradiology : AJNR, 2020)
[Display omitted] •A correlation between the susceptibility vessel sign (SVS) and red thrombi has been identified in MRI.•We hypothesized that the Embotrap allow better retrieving of SVS+ thrombi.•The VECTOR trial is a multicenter, prospective and randomized study designed to compare a first line strategy combining Embotrap added to contact aspiration (CA) versus CA alone in patients with SVS+ occlusions. A correlation between the susceptibility vessel sign (SVS) and red thrombi has been identified in MRI. We hypothesized that the Embotrap allow better retrieving of SVS+ thrombi. The AdaptatiVe Endovascular strategy to the CloT MRI in large intracranial vessel Occlusion (VECTOR) trial is a multicenter, prospective and randomized study designed to compare a first-line strategy combining Embotrap added to contact aspiration (CA) versus CA alone in patients with SVS+ occlusions.